(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To compare Surgical Outcomes in Involutional Entropion after Lateral tarsal strip procedure and Conventional everting Sutures procedure. Methods: This randomized controlled trial was conducted at the Department of Ophthalmology, Allied Hospital, Faisalabad, over six months. A total of 304 eyes (152 in each group) with primary involutional lower eyelid entropion were randomized to undergo LTS or CES. The primary outcome was surgical success, defined as complete resolution of entropion on postoperative day 1. Demographic and clinical characteristics were recorded, and subgroup analyses were performed. Results: The mean age was 60.2 ± 7.1 years, with 58.6% males. Day 1 success was achieved in 97.0% of eyes overall, with a higher rate in CES (100.0%) compared to LTS (94.1%), p = 0.002. Subgroup analysis demonstrated CES superiority across age groups, both genders, laterality, and in patients without ocular comorbidities. Symptom-based stratification also favored CES in multiple categories, including absence of blurry vision, presence of severe discomfort, and absence of redness (all p < 0.05). No major intraoperative or immediate postoperative complications occurred. Conclusion: CES demonstrated superior immediate anatomical correction compared to LTS in involutional entropion, with consistent benefits across clinical subgroups. While LTS remains valuable in recurrent or laxity-dominant cases, CES may be preferred for primary, uncomplicated presentations requiring rapid rehabilitation. Long-term studies are warranted to assess recurrence rates and durability.